Comparison the Executive Functions of Inhibition and Problem Solving in Adolescents with and Without Substance Abuse - Tahereh masoomi mofrad; Hamid Alizade; Ahmad Khamesan (Drug Control Headquarters, Research and Education Office, 2015)
Executive functions are self-regulated functions and show the ability to inhibition, self-changing, planning, organization, using the working memory, solving problems and targeting for homework and school activities. This study compares the executive functions of inhibition and problem solving in adolescents with and without substance abuse. In this causal-comparative study, 15 adolescents with substance abuse and 15 normal adolescents were selected which matched each other with the same age, sex and education. The research tools were Wisconsin Card, was used for assessing the inhibition executive functions, and Heppner and Petersen Questionnaires for problem solving. The results showed that there were statistically significant differences between groups between average score of inhibition executive functions and solving problem (except trend- avoid component). There were not statistically significant differences in the average score of inhibition executive functions and solving problem according to age, sex and education. It is concluded that the drug addicts are weaker than those without substance abuse based on the inhibition executive function and problem solving. These findings can be used for the prevention program.